Telemedicine in Low-Resource Settings - Richard Wootton (Frontiers Research Topics, 2015)
Telemedicine networks to support healthcare workers in resource-limited settings (often for humanitarian purposes) have evolved over the last decade or so in a largely autonomous way. Communication between them has been informal and relatively limited in scope. This situation could be improved by developing a comprehensive approach to the collection and dissemination of information.A recent review identified seven telemedicine networks, each of which had been in operation for at least five years and which provided store-and-forward telemedicine services to doctors in low- and middle-income countries. These networks provide clinically useful services and improved healthcare access. However, like much of telemedicine, the formal evidence for their cost-effectiveness remains weak.Topics of current research interest therefore include the cost-effectiveness of telemedicine in resource-limited settings. Outcomes data (and methods for gathering it) such as patient quality of life following a telemedicine episode, the knowledge-gain of healthcare staff involved in telemedicine, and staff recruitment and retention in rural areas are also of interest. Finally, there is little published information about the performance of these telemedicine networks (and methods for measuring it), about how best to manage them, and about how to share resources between them.A collection of articles reporting the current evidence supporting the use of telemedicine in resource-limited settings would build the evidence base and should provide a focus for future research. It would also serve to raise the profile of this potentially important research field.